Identifikasi Lapisan Akuifer Menggunakan Metode Seismik Refraksi di Desa Jatimulyo, Kecamatan Jati Agung, Kabupaten Lampung Selatan - Rhahmi Adni Pesma; Mokhammad Puput Erlangga; Intan Adiani Putri; Risky Martin Antosia; Ruhul Firdaus; Gestin Mey Ekawati (Engineering Faculty Universitas Lampung, 2020)
An initial subsurface survey to predict the aquifer is important to avoid the unprospect drill location and getting groundwater with the right discharge. In this study, prediction of the aquifer was carried out using the seismic refraction method in Jatimulyo Village, Jati Agung District, South Lampung Regency. The data was collected on October 6, 2019 using the SUMMIT X One seismic tool with 24 Geophones. The first break data from p-wave travel time is processed and interpreted using the Hagiwara method. Interpretation results show that there are three layers of subsurface lithology in the study area. The weathering layer was found at 2 m to 3.5 m depth with average velocity of 360 m/s. The second layer is dry sand with a velocity of 890 m/s at a depth of 2 m to 8 m. The third layer with a 2300 m/s velocity is a mixture of clay rock and saturated sand at depths of more than 8 m. As a comparison there is resistivity distribution data on the same measurement line in the study area. The overall interpretation shows that at a depth of 12 m with saturated clay sedimentary rock as a prospect of aquifer in this study area.